Effect of formula milk on the roughness and hardness of tooth enamel - Amaliyah Nur Irianti; Sri Kuswandari; Al Supartinah Santoso (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Demineralisation and remineralisation is a natural process in tooth enamel. It is influenced by the content of calcium and phosphorus in saliva, which concentrations are affected by the consumption of food, including formula milk. Demineralisation and remineralisation determine the roughness and hardness of the enamel surface. Purpose: This study compared the effect of formula milk on the roughness and hardness of tooth enamel. Methods: Maxillary premolar extracted teeth were demineralised with 37% phosphoric acid for 90 seconds and then divided into four treatment groups. For four days, the teeth were immersed twice a day in cow formula for five and ten minutes (Group I and II) and soy formula for five and ten minutes (Group III and IV). Before and after the immersion in milk, the teeth were submerged in artificial saliva. The enamel surface roughness and hardness were measured three times using a surface roughness tester and a Vickers microhardness tester, before and after demineralisation and after immersion in milk. Data were analysed using Kruskal–Wallis and post hoc Mann–Whitney tests. Results: There was no significant difference (p=0.88) observed in the roughness reduction among the treatment groups. The highest increase in hardness was noted for the ten-minute cow formula milk group (93.27 ± 16.00). The increase of hardness was higher after immersion for ten minutes. A substantial difference (p=0.03) was seen in the increase of hardness between the treatment groups. Conclusion: Immersion in cow and soy formula milk for five and ten minutes does not reduce the enamel roughness, but it increases the enamel hardness.